2008
DOI: 10.1177/000313480807401213
|View full text |Cite
|
Sign up to set email alerts
|

Early Thrombosis of the Superior Vena Cava in a Patient with a Central Venous Catheter and Carcinoma of the Ampulla of Vater

Abstract: Superior vena cava syndrome results from obstruction of flow through the vessel either by external compression or thrombosis. External compression by intrathoracic neoplasms is the most common etiology. Thrombosis of the vessel most often occurs in the setting of indwelling catheters or pacemakers. The diagnosis is suggested by the clinical manifestations of facial and upper extremity swelling, dyspnea, and cough. It is confirmed by CT scan showing the development of collateral flow around the lesion. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Only few papers have investigated the role of CT. Forneris reported on the use of helical CT in 18 hemodialyzed patients with a complicated indwelling internal jugular vein catheter (21). Cannon et al reported a case of CT-diagnosed superior vena cava thrombosis developing a short period after central venous catheterization and surgery for adenocarcinoma of Vater ampulla (22). Aggarwal and McCauley described a case of superior vena cava syndrome diagnosed by CT in a patient with tunneled CVD-induced thrombosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Only few papers have investigated the role of CT. Forneris reported on the use of helical CT in 18 hemodialyzed patients with a complicated indwelling internal jugular vein catheter (21). Cannon et al reported a case of CT-diagnosed superior vena cava thrombosis developing a short period after central venous catheterization and surgery for adenocarcinoma of Vater ampulla (22). Aggarwal and McCauley described a case of superior vena cava syndrome diagnosed by CT in a patient with tunneled CVD-induced thrombosis (23).…”
Section: Discussionmentioning
confidence: 99%